Training Needs of Member Fish Farmers of FFPOs in Purba Medinipur District of West Bengal - Abdul Hannan Mondal; Shyam Sundar Dana, Shyam Sundar Dana; Moumita Ray (Sarkar), Moumita Ray (Sarkar); Ritika Karjee, Ritika Karjee; Nilanjan Rej, Nilanjan Rej (Indian Journal of Extension Education, 2025)
The study assessed the training needs of fish farmers who are members of FFPO in the Purba Medinipur District of West Bengal in 2023. The study used a descriptive design, collecting primary data from 120 fish farmers across four FFPOs through semi-structured questionnaire and interviews. The study identified the key training needs of the FFPO members. The primary areas requiring attention included fish disease management (identification and control) (x̅ = 3.2), feeding strategies and feed formulation (x̅ = 3.02), water quality management (x̅ = 3.0), fish breeding (x̅ = 2.67), pond construction or renovation (x̅ = 2.65), marketing strategies (x̅ = 2.61), and selection of quality seed, species, and stocking density (x̅ = 2.52). Overall, most members exhibited medium (52.5%) to high (25.83%) training needs. There is a need for targeted training in these critical areas to improve fish-farming practices. Preferred trainers included private staff, input dealers, and medicine company representatives (77.5%), followed by fisheries institutes (65%) and government officials (40.83%). The study concluded that while FFPOs provide valuable training, there is a need for additional effort from other extension agencies to address the identified training gaps.